Honey: The Natural Inhibine” - Aliyazicioglu, Rezzan; Boukraa, Laid (Anti-Infective Agents, 2015)
Honey has been shown to contain glucose oxidase, which produces gluconic acid and hydrogen peroxide from glucose. Dilution of honey results in a significant increase in the activity of this molecule. Inhibine, an antibacterial substance previously described in honey, has been identified as hydrogen peroxide, which is manufactured at inhibine assay by the natural glucose oxidase in honey. Inhibine levels have been shown to be directly associated with hydrogen peroxide production.
Keywords: antimicrobial